Crystallographic structure of wild-type SARS-CoV-2 main protease acyl-enzyme intermediate with physiological C-terminal autoprocessing site - Jaeyong Lee (Nature Portfolio, 2020)
The SARS-CoV-2 main protease (Mpro) is one of two cysteine proteases essential for viral replication. Here, the authors determine the crystal structure of an Mpro acyl intermediate with its native C-terminal autocleavage sequence and the structure of a product bound active site mutant (C145A), which are of interest for antiviral drug development.